Relocation Stress Syndrome and Associated Health Outcomes among Older Persons Living in Long-Term Care Facilities: Findings from a Systematic Literature Review - Gouder, Jeannette Azzopardi; Sultana, Roberta; Fenech, Maria Aurora (Magyar Gerontológia, 2024)
Relocation stress syndrome was officially recognised as a nursing diagnosis in 1992; however, the phenomenon had been documented for at least 70 years. In Western literature, high mortality rates and other deleterious effects of relocation on older person populations were described as early as the 1960s.